Art embroidery as a way of formation of aesthetic culture of the future teachers of the fine arts (Pedagogy of Higher and Secondary Education, 2007)
In article ways of formation of aesthetic culture of the future teachers of the fine arts are considered.
Keywords: aesthetic culture; art embroidery